Efficacy of Trabectedin in Patients with Advanced Translocation‐Related Sarcomas: Pooled Analysis of Two Phase II Studies. (August 2017) - Takahashi, Mitsuru; Takahashi, Shunji; Araki, Nobuhito; Sugiura, Hideshi; Ueda, Takafumi; Yonemoto, Tsukasa; Morioka, Hideo; Hiraga, Hiroaki; Hiruma, Toru; Kunisada, Toshiyuki; Matsumine, Akihiko; Shimura, Masashi; et al.
Abstract: Background: Trabectedin is reported as effective, especially against translocation‐related sarcomas (TRSs) after failure of or intolerance to standard chemotherapy. We conducted two phase II studies of TRS, confirming high efficacy of 1.2 mg/m 2 trabectedin. The updated data of 66 patients in these studies was integrated to evaluate the efficacy of trabectedin against each histological subtype, and analyze final overall survival (OS). Methods: Trabectedin was administered on day one of a 21‐day cycle. Efficacy was assessed using progression‐free survival (PFS), OS, and best overall response. An analysis of OS and PFS was performed for subgroups divided by baseline lymphocyte count (<1, 000/μL, ≥1, 000/μL) or number of previous chemotherapy regimens (0, 1, 2, ≥3 regimens), and a Weibull parametric model was used to estimate the numerical relationship between lymphocyte count and PFS and OS. Results: Median PFS and OS in overall patients were 5.6 (95% confidence interval [CI]: 4.1–7.3) and 17.5 months (95% CI: 12.6–23.6), respectively. PFS in the myxoid and round‐cell liposarcoma (MRCL) group (7.4 months [95% CI: 5.6–11.1]) was longer than in the other subtypes. The response rate was also highest in the MRCL group. Median OS was longer in patients with baseline lymphocyte counts ≥1, 000/μL than in those with counts of <1, 000/μL, but median PFS was not different between the two subgroups. Conclusion: Our updated and pooled data showed that trabectedin exerted prolonged disease control and antitumor effects in patients with advanced TRS, especially in MRCL. We consider that the subgroup analyses also provide important information for trabectedin treatment in patients with TRS. Implications for Practice: The progression‐free survival (PFS) for the integrated data of 66 patients with translocation‐related sarcomas (TRSs) in two phase II studies of trabectedin 1.2 mg/m 2 was 5.6 months (95% confidence interval: 4.1–7.3). PFS and response rate in myxoid/round‐cell liposarcoma was longer than that of other subtypes. The overall survival (OS) in all TRS subtypes was similar to previous data of TRS patients. In subgroup analysis, the patients with baseline lymphocyte count ≥1, 000/μL exhibited better OS, although PFS was not different by baseline lymphocyte count. Our data are considered important information for trabectedin treatment in TRS patients. Abstract : This analysis updates the results of two phase II studies of translocation‐related sarcomas to evaluate the efficacy of trabectedin against histological subtype and analyze overall survival.